Об устойчивости решений динамических уравнений на основе функций разрывного типа - Бабенко, С.В.; Слынько, В.И. (Видавничий дім "Академперіодика" НАН України, 2009)
Дослiджено стiйкiсть розв’язкiв динамiчних рiвнянь на часовiй шкалi за допомогою функцiй розривного типу. Встановлено новi достатнi умови стiйкостi та асимптотичної стiйкостi розв’язкiв динамiчних рiвнянь. Stability of the solutions of dynamic equations on the time scales is considered by using the functions of the discontinuous type. The new sufficient conditions of stability and asymptotic stability of the solutions of dynamic equations are obtained.